1965
DOI: 10.1111/j.1471-4159.1965.tb10250.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phenylalanine Administration on the Free Amino Acids of Brain and Liver in the Rat

Abstract: RECENT studies have indicated that L-phenylalanine inhibits antibody response to diphtheria toxoid in rats and rabbits ( RYAN and CARVER, 1964). It was suggested, as an explanation for the inhibition, that excess phenylalanine caused a disturbance in the free amino acids of the animals with a resultant decrease in antibody (protein) synthesis. It is also conceivable that chronic alterations in the amino acids of the central nervous system induced by phenylalanine could also give rise to changes in protein synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1

Year Published

1967
1967
1984
1984

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 8 publications
3
9
1
Order By: Relevance
“…The only well understood mechanism underlying chemical alterations in the brains of phenylketonurics, and of animal models of the disease, is the inhibition by excess phenylalanine of the cerebral uptake of amino acids sharing a common transport system (3,6,33,41). The present results show that this mechanism is operative in the 22-day-old fetus as well (see methionine, leucine, isoleucine and valine in Table 4).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The only well understood mechanism underlying chemical alterations in the brains of phenylketonurics, and of animal models of the disease, is the inhibition by excess phenylalanine of the cerebral uptake of amino acids sharing a common transport system (3,6,33,41). The present results show that this mechanism is operative in the 22-day-old fetus as well (see methionine, leucine, isoleucine and valine in Table 4).…”
Section: Discussionsupporting
confidence: 52%
“…Observations on blood sampled at different times throughout the day indicated that this indeed was the case. The plasma phenylalanine levels of the pregnant rats on the experimental diet were highest during the dark period (i.e., at midnight, 2 A.M. or 6 A.M.). They were 30-50 and 6Wo lower at 10 P.M. and 6 P.M., respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that brain total alpha-amino nitrogen was not altered in these experiments, despite elevated phenylalanine and tyrosine, indicates that aggravated imbalance of other brain amino acids cau occur in animals with raised pheuylalanine levels (cf. Carver, 1965;Boggs and McKean. 1965).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of aniino acids in brain is very sensitive to phenylalanine levels as shown by changes in the brain free aniino acids content caused by a single injection of i.-phcnylalaninc [3]. In our experiments, prolonged high levels of phenylalanine in plasma and correspondingly high concentration in the brain resulted in a pronounced increase in tyrosinc in brain and in a significant depletion of cerebral pools of valine, methionine, isoleucine, and leucine.…”
mentioning
confidence: 63%